Molecular Genetics of Liver Neoplasia - Wang, Xin Wei.; Wang, Xin Wei.; Grisham, Joe W.; Grisham, Joe W.; Thorgeirsson, Snorri S.; Thorgeirsson, Snorri S. (Cancer Genetics,, 2011)
Cancer is a genetic disease and cancer research is a broad discipline embracing investigators and clinicians with diverse backgrounds. This new edition of Molecular Genetics of Liver Neoplasia intends to provide a comprehensive view on genetics and a mechanistic understanding of liver cancer. The book covers from molecular pathogenesis and cellular origin to translational genomics of liver cancer. The leading experts in the field of liver cancer have thoroughly summarized the latest developments and have provided current viewpoints and novel concepts. This cutting-edge volume is a vital resource for today’s basic cancer researchers, graduate students, medical students and clinicians interested in hepatocarcinogenesis.